2017
DOI: 10.1103/physrevb.95.180404
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Haldane phase in the S=1 bilinear-biquadratic Heisenberg model on the square lattice

Abstract: Infinite projected entangled pair states simulations of the S = 1 bilinear-biquadratic Heisenberg model on the square lattice reveal an emergent Haldane phase in between the previously predicted antiferromagnetic and 3-sublattice 120 • magnetically ordered phases. This intermediate phase preserves SU(2) spin and translational symmetry but breaks lattice rotational symmetry, and it can be adiabatically connected to the Haldane phase of decoupled S = 1 chains. Our results contradict previous studies which found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 69 publications
1
36
1
Order By: Relevance
“…Moreover, in our recent study of the spin-1 BBH model on the square lattice [27,28], we found the occurrence of a quantum paramagnetic phase in between the antiferromagnetic and 120 • magnetically ordered phases, and we were able to show that this phase can be adiabatically connected to the one-dimensional Haldane phase of decoupled spin-1 chains. In addition, we also encountered a partially-magnetic partially-quadrupolar phase in between the antiferroquadrupolar and ferromagnetic phases.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Moreover, in our recent study of the spin-1 BBH model on the square lattice [27,28], we found the occurrence of a quantum paramagnetic phase in between the antiferromagnetic and 120 • magnetically ordered phases, and we were able to show that this phase can be adiabatically connected to the one-dimensional Haldane phase of decoupled spin-1 chains. In addition, we also encountered a partially-magnetic partially-quadrupolar phase in between the antiferroquadrupolar and ferromagnetic phases.…”
Section: Introductionmentioning
confidence: 53%
“…Inspired by our finding [27] of the one-dimensional Haldane phase extending all the way to the two-dimensional isotropic limit on the square lattice, we searched for signs of a possible quantum paramagnetic phase on the triangular lattice. The simple update results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The emergence of a quasi-one-dimensional Haldane phase in a narrow region between the Néel and AFM3 phases was also reported. 8 The phase diagram for the honeycomb lattice includes the FM, FQ, Néel, and plaquette valence-bond-solid phases. 9 For the triangular lattice, the phase diagram contains the FM, FQ, 120 • -structure antiferromagnetic (120 • -AFM), and AFQ3 phases.…”
Section: (A)mentioning
confidence: 99%